2011
DOI: 10.1002/anie.201006880
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Elansolid Biosynthesis: Evidence for an Unprecedented Quinone Methide Initiated Intramolecular Diels–Alder Cycloaddition/Macrolactonization

Abstract: Elansolids A1/A2 (1) [1] and B1-B3 (2-4) and the structurally unusual and highly reactive elansolid A3 (5) [2] are new metabolites from the gliding bacterium Chitinophaga sancti (formerly Flexibacter spec.; Scheme 1). While elansolid A2 (1*) shows antibiotic activity against Gram-positive bacteria in the range of 0.2 to 64 mg mL À1 and cytotoxicity against L929 mouse fibroblast cells with an IC 50 value of 12 mg mL À1 , the atropisomer elansolid A1 (1) is significantly less active. [2,3] The elansolids featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 22 publications
1
55
0
Order By: Relevance
“…In our previous report, we showed that 1 and 1* differ in their biological activity 1. Both showed the lowest MIC against M. luteus (MIC 0.3 μg mL −1 for 1* , 1 was less active); against methicillin‐resistant S. aureus MRS3, 1* had a MIC of 4.2 μg mL −1 while 1 showed no growth inhibition up to 33 μg mL −1 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In our previous report, we showed that 1 and 1* differ in their biological activity 1. Both showed the lowest MIC against M. luteus (MIC 0.3 μg mL −1 for 1* , 1 was less active); against methicillin‐resistant S. aureus MRS3, 1* had a MIC of 4.2 μg mL −1 while 1 showed no growth inhibition up to 33 μg mL −1 .…”
Section: Resultsmentioning
confidence: 94%
“…Both showed the lowest MIC against M. luteus (MIC 0.3 μg mL −1 for 1* , 1 was less active); against methicillin‐resistant S. aureus MRS3, 1* had a MIC of 4.2 μg mL −1 while 1 showed no growth inhibition up to 33 μg mL −1 . Noteworthy, elansolid A2 ( 1* ) and the quinone methide A3 ( 7 ) had identical MICs, but differed in their cytotoxicity:2 against the mouse fibroblast cell line L929, 1* showed cytotoxicity at 12 μg mL −1 , 7 was less toxic (33 μg mL −1 ), and 1 was nontoxic up to 40 μg mL −1 1. 2…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples of de novo non-enzymatic natural products synthesis include jadomycin (DNA alkylator) 20 , elansolid (antibiotic) 21 and the ammosamides (quinone reductase 2 inhibitors, myosin modifiers). 22 In these examples, the non-enzymatic reaction pathway has been exploited to generate analogs with enhanced biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…In situ cycloisomerization of 70 and simultaneous dehydration and dearomatization of a synthon corresponding to 71 would produce exocyclic enol ether (74) and o-quinone methide (75), respectively. These would be primed for intermolecular hetero-Diels-Alder cycloaddition to assemble the berkelic acid skeleton 102 . Indeed, these transformations worked under Ag(I) catalysis in one pot, and, after deprotection, berkelic acid was obtained in good yield (Fig.…”
Section: Nm) Isolated From Amentioning
confidence: 99%